Synthesis of nanoparticles of Poly (ethyleneimine) and their characterization by transmission electron microscopy, thin layer chromatography, and infrared spectroscopy - Bashyal, R. (Journal of Agriculture and Forestry University, 2022)
Intracellular gene delivery alters the expression of a gene and corrects a defective gene that may be the cause of a disease or a disorder. Nonviral gene delivery is more appropriate than viral-mediated due to their low cytotoxicity and immunogenicity. Amongst these, polycationic nanoparticles i.e. Polyethyleneimine (PEI) were used most successfully. The PEGylation of such cationic polymer reduces its cytotoxicity. Different molecular weight poly (ethylene glycol) was used for the PEGylation of such cationic nanoparticles which have an individual effect. For this purpose, the PEG is esterified, which was then reacted with a cationic polymer. Four different molecular weights of PEG were used. The size of nanoparticles so formed depends upon the molecular weight of PEG. So formed nanoparticles were dialyzed, lyophilized, and then characterized by IR and TEM. The nanoparticles so formed are directly affected by the different molecular weights of PEG. Higher the molecular weights of PEG smaller size of nanoparticles so formed but only up to a limited extent. The decreasing order of nanoparticles as an increment of molecular weight of PEG was found as a -0.85 coefficient of correlation. The smaller-sized nanoparticles have higher transfection efficiency than larger-sized nanoparticles. So, the higher the molecular weight of PEG higher will be the transfection efficiency.